2013
DOI: 10.1182/blood-2012-12-469544
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function of the protein kinase C δ (PKCδ) causes a B-cell lymphoproliferative syndrome in humans

Abstract: • Mutations in PRKCD cause a syndrome characterized by chronic benign lymphadenopathy, positive autoantibodies, and NK dysfunction.• PRKCD deficiency disrupts control of B-cell proliferation and apoptosis and affects NK-cell cytolytic activity.Defective lymphocyte apoptosis results in chronic lymphadenopathy and/or splenomegaly associated with autoimmune phenomena. The prototype for human apoptosis disorders is the autoimmune lymphoproliferative syndrome (ALPS), which is caused by mutations in the FAS apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 20 publications
2
113
0
Order By: Relevance
“…Signaling molecule PKCd controls B-cell anergy and its deficiency impairs B-cell tolerance, leading to autoantibody production in humans and mice. 11,19,20 Unmanipulated PKCd-deficient mice spontaneously produced significantly higher levels of PF4/ heparin-specific IgMs than wild-type controls ( Figure 2B). A significantly higher number of unmanipulated PKCd-deficient mice also spontaneously produced elevated levels of PF4/heparin-specific IgGs relative to wild-type controls ( Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Signaling molecule PKCd controls B-cell anergy and its deficiency impairs B-cell tolerance, leading to autoantibody production in humans and mice. 11,19,20 Unmanipulated PKCd-deficient mice spontaneously produced significantly higher levels of PF4/ heparin-specific IgMs than wild-type controls ( Figure 2B). A significantly higher number of unmanipulated PKCd-deficient mice also spontaneously produced elevated levels of PF4/heparin-specific IgGs relative to wild-type controls ( Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…PKC␦ Ϫ/Ϫ mice represent a lupus mouse model in which this checkpoint is severely impaired, and its relevance in human disease is underscored by three recent reports of human patients with mutations in PKC␦ that underlie juvenile-onset SLE, autoimmune lymphoproliferative syndrome (ALPS), and B cell deficiency with autoimmunity, with some of these patients displaying defective B cell apoptosis and hyperpro- liferation of transitional B cells (3)(4)(5). The striking resemblance of the disease in these patients to the phenotypes we have characterized in the PKC␦ Ϫ/Ϫ mice highlights the relevance of these mice as a model of human disease that warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…PKC␦-deficient mice develop a severe autoimmune disease characterized by autoantibody production, glomerulonephritis, and robust B cell lymphoproliferation leading to splenomegaly and lymphadenopathy (1,2). Several recent reports have identified mutations in PKC␦ that appear to underlie autoimmune pathology in humans (3)(4)(5), supporting the notion that PKC␦ Ϫ/Ϫ mice represent a valuable mouse model of human disease. Although PKC␦ clearly has a vital function in suppressing autoimmune disease in both mice and humans, the mechanisms by which PKC␦ deficiency causes autoimmunity remain poorly defined.…”
mentioning
confidence: 92%
“…PKC-δ-deficient mice represent elevation of a B-cell lineage-specific expansion, such as naïve and activated follicular mature B cells, and also show defective B-cell tolerance to self-antigens [121,122]. In humans, PKC-δ deficiency is known as a genetic defect leading to B-cell deficiency, impaired apoptosis, and consequently to SLE [123,124]. Salzer et al [125] reported a patient with a PKC-δ mutation who was suffering from recurrent infections and severe SLE as well as autoimmune disorders such as membranous glomerulonephritis and antiphospholipid syndrome.…”
Section: Autoimmunity In Padsmentioning
confidence: 99%